1993
DOI: 10.1093/bja/71.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Sinus Arrhythmia: A New, Objective Sedation Score

Abstract: We tested if microcomputer-based measurements of heart rate variability and respiratory sinus arrhythmia (RSA) could be used as the basis of an objective sedation score. Measurements were obtained in eight ICU patients before, during and after physiotherapy. Patients were sedated with propofol and alfentanil and paralysed with atracurium. Mean ECG R-R interval showed little variation, changing from 646.15 (SD 203.15) ms to 596.08 (181.75) ms and 633.98 (184.53) ms before, during and after physiotherapy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This has led to speculation that HRV could be used to monitor the depth of anaesthesia, and particularly to avoid superficial levels of anaesthesia [83]. This idea is supported by the increase in HRV that is seen with surgical stimuli or intubation and at the end of anaesthesia [84][85][86]. But these results have been interpreted in different ways.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…This has led to speculation that HRV could be used to monitor the depth of anaesthesia, and particularly to avoid superficial levels of anaesthesia [83]. This idea is supported by the increase in HRV that is seen with surgical stimuli or intubation and at the end of anaesthesia [84][85][86]. But these results have been interpreted in different ways.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…RSA diminishes during propofol sedation [64], propofol anaesthesia [65] and isoflurane anaesthesia [66] and therefore it has been suggested that measurement of RSA could be a useful index of anaesthetic depth. Changes in RSA however depend upon the activity of the brainstem and the action of the anaesthetic agents thereupon, yet consciousness and memory arise from higher centres within the central nervous system.…”
Section: Respiratory Sinus Arrhythmiamentioning
confidence: 99%
“…It has been suggested that the depth of anaesthesia has an effect on the function of the autonomic nervous system. Several groups have claimed that monitoring heart rate variability, and RSA in particular, is useful in determining the depth of anaesthesia [5][6][7][8][9]. Numerous indices have been derived to describe the overall variation in heart rate [10].…”
Section: Introductionmentioning
confidence: 99%